2015
DOI: 10.1016/j.ejphar.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Amitifadine, a triple monoamine re-uptake inhibitor, reduces nicotine self-administration in female rats

Abstract: A wider diversity of drug treatments to aid smoking cessation is needed to help tailor the most efficacious treatment for different types of smokers. This study was conducted to determine whether amitifadine, which inhibits re-uptake of dopamine, norepinephrine and serotonin, would decrease nicotine self-administration at doses that do not cause adverse side effects. Adult female Sprague-Dawley rats were trained to self-administer nicotine intravenous (IV) and were given acute doses of amitifadine in a repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Previously we found that the nicotinic partial agonist sazetidine-A has a more prominent effect reducing nicotine self-administration later in the session {Johnson et al, 2012). In contrast, we found that the monoamine uptake inhibitor amitifadine had greater efficacy during the beginning of the test session {Levin et al, 2014). Therefore, we hypothesized that the nicotinic partial agonist varenicline would decrease nicotine self-administration preferentially during the later part of the session while the monoaminergic reuptake inhibitor bupripion would preferentially decrease nicotine self-administration during the initial part of the session.…”
Section: Introductionmentioning
confidence: 85%
“…Previously we found that the nicotinic partial agonist sazetidine-A has a more prominent effect reducing nicotine self-administration later in the session {Johnson et al, 2012). In contrast, we found that the monoamine uptake inhibitor amitifadine had greater efficacy during the beginning of the test session {Levin et al, 2014). Therefore, we hypothesized that the nicotinic partial agonist varenicline would decrease nicotine self-administration preferentially during the later part of the session while the monoaminergic reuptake inhibitor bupripion would preferentially decrease nicotine self-administration during the initial part of the session.…”
Section: Introductionmentioning
confidence: 85%
“…When tested during the co-use phase, varenicline specifically decreased nicotine-reinforced lever pressing, without altering inactive lever pressing, EtOH consumption or water consumption. Although several studies have demonstrated that varenicline reduces EtOH consumption in humans (Falk et al 2015; Litten et al 2013; McKee et al 2013), conflicting evidence for the effects of varenicline on EtOH craving and consumption has been reported (de Bejczy et al 2015; Schacht et al 2014; Verplaetse et al 2016). In conflict with the results of the current study, several preclinical studies have also demonstrated that pretreatment with varenicline reduces EtOH consumption in rodents (Froehlich et al 2017; Kamens et al 2010; Sotomayor-Zarate et al 2013; Steensland et al 2007) when EtOH was available in the absence of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…16 We showed that amitifadine given either acutely or chronically significantly reduces nicotine self-administration in rats. 13 Amitifadine also significantly reduces ethanol consumption in rats 14 and reduces binge drinking and impulsivity in mice 17 On the basis of our previous findings, 13 we hypothesized that the combination of nicotine infusion plus amitifadine would provide greater and more persistent reductions in nicotine selfadministration than amitifadine alone. Chronic nicotine infusions would serve to keep nicotinic receptors desensitized blunting the effects of nicotine self-administration, whereas chronic amitifadine as a triple reuptake inhibitor would provide a higher tone of dopamine, serotonin, and norepinephrine blunting the consequence nicotine-induced catecholamine release.…”
Section: Introductionmentioning
confidence: 94%
“…This dose of amitifadine previously shown to significantly reduce nicotine selfadministration in rats. 13 Each solution was injected subcutaneously in a volume of 1 ml/kg body weight. Thus, each animal received injections of saline or amitifadine while chronically receiving subcutaneous infusion of nicotine or saline, during self-administration trials, as well as the period during nicotine self-administration abstinence.…”
Section: Amitifadine Injectionsmentioning
confidence: 99%
See 1 more Smart Citation